EXTENSI APLIKASI QUIZ ONLINE PADA MOODLE VERSI MOBILE - Wijaya, Pieter Sindu; Lim, Resmana; Andjarwirawan, Justinus (Jurnal Infra, 2014)
Learning Management System application is currently widely used by many people to conduct learning activities without having to be in a classroom . The use of Moodle as a Learning Management System be benefited a lot. Moodle is equipped with a mobile application that can be installed on Android devices. However, this application has many features that can be used, some of the existing features is to look at the class that followed and quizzes are held. By utilizing web services, an application designed to address the shortcomings of existing applications. This application provides classes and quiz creation feature on mobile devices. Users who are registered as holding quizzes and teachers can create questions over and Android device users can be registered for the quiz via Android devices. Based on the testing results, this application can working properly on Android versions 4.0 - 4.3 or Jelly Bean and web services that can be used in sync with applications on the web.Â catatan:Fulltext paper ini di publikasikan pada prosiding Seminar Nasional